(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
There exist numerous mine sites in India where surface blasting is carried out in close vicinity of underground coal mines, which has a potential risk of damage to the underground mine structures and persons deployed underground. In coming years, there will be more number of mine sites where surface mines will be limited up to depth of 300 m to economise in terms of handling overburden/waste due to high stripping ratio, environmental conditions imposed by regulatory agencies and unviable cost of production. This paper deals with an Indian case study where blast induced damage was estimated on roof of the underground structures due to blasting carried at neighbouring surface mine. A new approach is proposed to classify damage of underground structures due to surface blasting using the concept of “Blast Damage Factor (BDF)” and linear discriminant functions. BDF is defined in terms of induced stress, damage resistance, together termed as Strength Factor, and another dimensionless indicator of damage as Mining Factor. The damage types are classified into three groups as "Severe, Moderate and No damage". It was inferred from data analysis that the threshold site specific values of BDF for Severe damage was arrived as BDF≥3.85, Moderate damage as 1.79≤BDF<3.85 and No damage as BDF<1.79. The BDF, when converted to peak particle velocity corresponds to PPV ≥ 51 mm/s in respect of Severe damage, 24 mm/s ≤ PPV<51 mm/s in respect of Moderate damage and PPV < 24 mm/s in respect of No damage. Site-specific charts between charge weight and distance have been developed so that estimation of damage type due to impact of surface blasting on neighbouring underground mine may be carried out easily by practising blasting engineer.